The expected benefits of using social robots when working with institutionalised older adults: A qualitative study among healthcare professionals - Sanja Balalic; Robbert Sanderman; Nick Degens; Marrit Tuinman; Mariët Hagedoorn (PLoS ONE, 2026)
The shortage of healthcare professionals increasingly challenges the provision of care for institutionalised older adults. This study investigates healthcare professionals’ expectations regarding the added value of social robots in daily care, as their perspective is adamant for implementation of these robots but not yet fully investigated. Two consecutive focus group sessions were conducted across three nursing homes with 24 healthcare professionals. The first session focused on identifying potential ways in which social robots could add value for both staff and residents. After sharing suggestions across all groups, the second session facilitated cross-validation and in-depth discussion of practical implications. Data were analysed using qualitative thematic analysis. Healthcare professionals expected several benefits from using a social robot, including reduced workload and mental strain, improved work atmosphere, and potentially heightened job satisfaction. For residents, expected benefits included promotion of self-care and self-reliance through reminders and notifications, and provision of companionship during lonely periods. Reported possible barriers included limited technical knowledge and lack of support from residents’ families. Participants expected that social robots could help save time and energy, enabling more focused attention on residents needing support—even those who may not actively seek it. Professionals indicated that this might enhance both residents’ well-being and the quality and satisfaction of their own work. Implementing some of the specific suggestions from professionals merits further investigation.